2019
DOI: 10.3390/nu11030501
|View full text |Cite
|
Sign up to set email alerts
|

Subjects’ Perception in Quantifying Printed and Digital Photos of Food Portions

Abstract: Although digital photos have the potential to improve the precision of reported portions in dietary assessment, there are few studies investigating its accuracy in comparison to printed photos. The aim of this study was to evaluate the perception of adults in quantifying food portion sizes using printed and digital photos, displayed on computer-screens and tablets. In total, 1165 evaluations were performed for 60 photos of portion sizes in Brazil. Each participant (n = 58) attended two sessions in the study ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…We found that our digitally displayed PSEA did not have sufficient accuracy to be scaled up in Malawi in their current form. This finding is consistent with recent results from Brazil showing that digital PSEA displayed on a tablet led to more underestimation than other methods (19) . However, given that these are the first studies in LMIC to validate digitally displayed photographic PSEA, we expect that future studies could refine digital PSEA to improve accuracy for estimating usual individual intakes or intake of specific nutrients and for measuring differences in intakes between groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that our digitally displayed PSEA did not have sufficient accuracy to be scaled up in Malawi in their current form. This finding is consistent with recent results from Brazil showing that digital PSEA displayed on a tablet led to more underestimation than other methods (19) . However, given that these are the first studies in LMIC to validate digitally displayed photographic PSEA, we expect that future studies could refine digital PSEA to improve accuracy for estimating usual individual intakes or intake of specific nutrients and for measuring differences in intakes between groups.…”
Section: Discussionsupporting
confidence: 93%
“…Although our study had some limitations, digitally displayed photographic PSEA could be improved with further testing and the advantages and disadvantages of using different types of PSEA should be considered. Our findings showed that digitally displayed and print photographic PSEA were comparable, which is consistent with findings from two studies in the USA (35,36) and one from Brazil (19) . This indicates that even in a setting with low media exposure, digitally displayed PSEA can be used interchangeably with printed food atlases of the same dimensions, provided the accuracy of the PSEA is adequate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In Brazil, an adapted version of the software together with a photograph manual for food portion sizes is available (7) . Nonetheless, when we assessed the ability of individuals to quantify some of those photographs, we noticed larger errors among low-educated individuals compared with other population groups (8) . Although individuals are cognoscenti (9) and education level is usually considered not to be a limiting factor for the R24h (10) , the level of education seemed to influence the ability of those interviewed to inform their food intake.…”
mentioning
confidence: 86%